Analysis and mining of adverse events associated with vorapaxar: A FAERS database-based study - Hui Zhang; Minghao Lin; Chaoqun Song; Zheng Nan; Dexi Zhao; Yujuan Fu (PLoS ONE, 2026)
Objective Vorapaxar is a platelet protease-activated receptor-1 antagonist that can inhibit thrombin- and thrombin receptor agonist peptide-induced platelet aggregation. This study aims to explore the potential medication risks of vorapaxar through data mining of its related adverse events, thereby providing a more rational and safe reference for clinical medication. Methods In this study, adverse event reports related to Vorapaxar were retrieved and extracted from the FAERS database covering the 2004 Q1to 2024 Q4. The primary method employed was the reporting odds ratio (ROR) approach, which was used to detect risk signals associated with Vorapaxar. Results A total of 185 adverse event reports were included in this study, among which male cases accounted for 52%, higher than the proportion of female cases. Most reports were submitted by consumers, and the majority of these reports originated from the United States. Screening of Vorapaxar identified 162 preferred terms (PTs), most of which were consistent with the adverse reaction information of Vorapaxar already published by the U.S. Food and Drug Administration (FDA). Conclusion The adverse events involved 19 organ systems. Reports on vascular diseases, neurological diseases, and other conditions were numerous with strong signals, which were consistent with the drug instructions. Among them, vascular diseases had the highest risk of positive signals, including various hemorrhagic events and vascular structural/functional abnormalities. These findings suggest that clinical practice should be alert to adverse reactions in the vascular system, especially bleeding and severe vascular structural abnormalities.